2002
DOI: 10.1097/00042737-200204000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural characteristics of distal duodenum mucosa in patients with cirrhosis

Abstract: The epithelial layers from cirrhotic patients show ultrastructural abnormalities. However, it is not known if the observed alterations are related to the presence of increased intestinal permeability or to bacterial translocation, which are frequently found in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0
2

Year Published

2004
2004
2012
2012

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 20 publications
2
48
0
2
Order By: Relevance
“…Cytokines such as IL-1β and TNF are known to cause a disruption of tight junctions [45] . In one study, distension of the intercellular s�aces below these tight junctions was observed in duode� nal bio�sies of cirrhotic �atients [46] . Alcoholic �atients without liver cirrhosis that cease alcohol consumption demonstrated higher intestinal permeability in 3 d by way of a chro�iu��51�EDTA absor�tion test.…”
Section: Disruption Of the Intestinal Barrier Function As Mechanism Fmentioning
confidence: 97%
“…Cytokines such as IL-1β and TNF are known to cause a disruption of tight junctions [45] . In one study, distension of the intercellular s�aces below these tight junctions was observed in duode� nal bio�sies of cirrhotic �atients [46] . Alcoholic �atients without liver cirrhosis that cease alcohol consumption demonstrated higher intestinal permeability in 3 d by way of a chro�iu��51�EDTA absor�tion test.…”
Section: Disruption Of the Intestinal Barrier Function As Mechanism Fmentioning
confidence: 97%
“…The pathophysiologic mechanisms are not totally understood and several factors may be involved. Malabsorption has been implicated and this was presumed to be related to changes in the SB villi [2,4,5] . For example, Such et al [4] investigated 6 patients with cirrhosis using jejunal biopsies, and studied the mucosa under electron microscopy.…”
Section: Discussionmentioning
confidence: 99%
“…Malabsorption has been implicated and this was presumed to be related to changes in the SB villi [2,4,5] . For example, Such et al [4] investigated 6 patients with cirrhosis using jejunal biopsies, and studied the mucosa under electron microscopy. The authors observed that "the microvilli were reduced in number and appeared shorter and thicker when compared to controls", and their conclusion was that "the total absorptive surface may be reduced in cirrhotic patients".…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations